School‐based anti‐bullying approaches for children and young people with special educational needs and disabilities: a systematic review and synthesis - Badger, JR; Nisar, A; Hastings, RP (Wiley, 2024)
Mainstream anti-bullying interventions can reduce primary school-level victimisation by 15–16% and bullying perpetration by 19%–20% (Aggression and Violent Behavior, 2019; 45: 111–133). Less is known about anti-bullying interventions for pupils with special educational needs and disabilities (SEND) even though they are at least 2–4 times more likely to be involved in bullying. This systematic review aimed to identify reported anti-bullying approaches for pupils with SEND, what the evidence is for these approaches reducing bullying and which design factors are linked to a reduction in bullying. We searched 10 databases and four grey literature sources for articles that evaluated school-based anti-bullying strategies for children and young people aged 4–18 years with SEND. This review included 15 studies and used the Mixed Methods Appraisal Tool for quality and risk of bias. Ten reported a reduction in bullying involvement, but the evidence was variable. A further 27 articles formed a ‘suggested strategies’ review which synthesised articles without evaluations of interventions but that suggested anti-bullying strategies for use with pupils with SEND. The main suggestion was encouraging social skills and networks. Interventions should be evaluated for feasibility, acceptability and effectiveness. High-quality randomised controlled trials are required to build an evidence base to support pupils with SEND.